2019
DOI: 10.3389/fpls.2019.01607
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating Vigna Stipulacea: A Potential Legume Crop With Broad Resistance to Biotic Stresses

Abstract: Though crossing wild relatives to modern cultivars is a usual means to introduce alleles of stress tolerance, an alternative is de novo domesticating wild species that are already tolerant to various kinds of stresses. As a test case, we chose Vigna stipulacea Kuntze, which has fast growth, short vegetative stage, and broad resistance to pests and diseases. We developed an ethyl methanesulfonate–mutagenized population and obtained three mutants with reduced seed dormancy and one with reduced pod shattering. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…The lupin genus (Lupinus) is relatively large, with approximately 280 species (Wolko et al, 2011). Four lupin species have been domesticated: the two ancient domesticates white lupin (Lupinus albus) of the Mediterranean, tarwi Gladstones (1967), Koinange et al (1996), Isemura et al (2010Isemura et al ( , 2012, Talukdar (2011), Funatsuki et al (2014, Murgia et al (2017), Dong et al (2017aDong et al ( , 2017b, Takahashi et al (2019Takahashi et al ( , 2020, Aguilar-Benitez (2020) Strengthening of the dehiscence zone Reduced shattering G. max, L. angustifolius, L. luteus, L. digitatus, V. sativa, V. stipulacea Gladstones (1967), Dong et al (2014Dong et al ( , 2017a, Takahashi et al (2019) The absence of pod wall fiber Loss of shattering, pod nontwisting, dehiscence not leading to seed release P. vulgaris, P. sativum, V. villosa, V. Unguiculata Emerson (1904), White (1917), Blixt (1978), Koinange et al (1996), Myers et al (2001), Murgia et al (2017), Kissing Kucek et al (2020) Major reduction in suture fiber Loss of shattering, string formation often temperature-dependent P. vulgaris, P. sativum Emerson (1904), Wellensiek (1971), McGee and Baggett (1992), Koinange et al (1996), Hagerty et al (2016) (Lupinus mutabilis Sweet) of the Andes, as two European species domesticated since the 19th century, annual yellow lupin (Lupinus luteus) and narrow-leaf lupin (Lupinus angustifolius). A reduction in pod dehiscence has occurred in all of these species, which has often been highly parallel (Wolko et al, 2011;Atchison et al, 2016;Gresta et al, 2017).…”
Section: Lupinus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…The lupin genus (Lupinus) is relatively large, with approximately 280 species (Wolko et al, 2011). Four lupin species have been domesticated: the two ancient domesticates white lupin (Lupinus albus) of the Mediterranean, tarwi Gladstones (1967), Koinange et al (1996), Isemura et al (2010Isemura et al ( , 2012, Talukdar (2011), Funatsuki et al (2014, Murgia et al (2017), Dong et al (2017aDong et al ( , 2017b, Takahashi et al (2019Takahashi et al ( , 2020, Aguilar-Benitez (2020) Strengthening of the dehiscence zone Reduced shattering G. max, L. angustifolius, L. luteus, L. digitatus, V. sativa, V. stipulacea Gladstones (1967), Dong et al (2014Dong et al ( , 2017a, Takahashi et al (2019) The absence of pod wall fiber Loss of shattering, pod nontwisting, dehiscence not leading to seed release P. vulgaris, P. sativum, V. villosa, V. Unguiculata Emerson (1904), White (1917), Blixt (1978), Koinange et al (1996), Myers et al (2001), Murgia et al (2017), Kissing Kucek et al (2020) Major reduction in suture fiber Loss of shattering, string formation often temperature-dependent P. vulgaris, P. sativum Emerson (1904), Wellensiek (1971), McGee and Baggett (1992), Koinange et al (1996), Hagerty et al (2016) (Lupinus mutabilis Sweet) of the Andes, as two European species domesticated since the 19th century, annual yellow lupin (Lupinus luteus) and narrow-leaf lupin (Lupinus angustifolius). A reduction in pod dehiscence has occurred in all of these species, which has often been highly parallel (Wolko et al, 2011;Atchison et al, 2016;Gresta et al, 2017).…”
Section: Lupinus Sppmentioning
confidence: 99%
“…The independent evolution of similar characteristics has been achieved through selection at orthologous loci. Takahashi et al (2019) recently evaluated pod shattering in the biotic stress-resistant legume Vigna stipulacea using mutant populations. The authors identified mutant lines with reduced shattering and selected a mutant (rps1) with a total loss of pod shattering.…”
Section: Other Vigna Sppmentioning
confidence: 99%
“…Out of the 57 candidate genes, 18 genes encode transcription factors like AP2/ERF, WRKY, and NAC, whereas the rest of the genes were involved in cellulose synthase and serine/threonine protein kinase. The candidate genes for pod shattering have also been identified in other legumes including Vigun02g095200 (cellulose synthase), Vigun03g306000 (NAC domain transcription factor), and zombi pea (Suanum et al, 2016;Lo et al, 2018;Takahashi et al, 2019;Amkul et al, 2020;Watcharatpong et al, 2020). In Sorghum propinquum, WRKY modulates the flower and seed development and lignin deposition, and it is also found to be involved in pod shattering (Tang et al, 2013).…”
Section: Candidate Gene Identification For Seed Development-related Traitsmentioning
confidence: 99%
“…However, almost all the efforts and resources invested in agriculture during the last century were focused on improving the yield, resistance and quality of a few specific staple crops. Neglected landraces are regarded as having interesting potential, and recent studies have demonstrated that some wild legumes can be an important target to develop modern functional foods because they possess various bioactive molecules that interact positively with human health [2][3][4][5]. Among these, members of the Vigna genus show a growing social and economic importance in several African regions, especially where the local population is not able to afford animal proteins [6][7][8].…”
Section: Introductionmentioning
confidence: 99%